Pengaruh Pemberian Tepung Kulit Labu Kuning Terfermentasi Dalam Ransum Terhadap Pertumbuhan Ayam Kampung Super Umur 3-10 Minggu - Oldilia Kurniati; I Gusti Agus Putra Sanjaya; Ni Made Yudiastari (Fakultas Pertanian, Universitas Warmadewa, 2026)
The need for raw materials for poultry rations has obstacles such as competing with human needs, relatively expensive prices and raw materials are still imported.Therefore, it is necessary to use alternative feed ingredients, one of which is by utilizing Yellow Pumpkin Skin. This study aims to determine the effect of giving fermented yellow pumpkin husk flour in rations on the growth of super free-range chickens aged 3-10 weeks and to find out at what level the administration of fermented yellow pumpkin husk waste flour affects the growth of super free-range chickens aged 3-10 weeks. The design used in this study was the Complete Random Design (RAL) which consisted of 5 treatments and 3 replicas. The treatment used was P0 = Chicken without fermented pumpkin peel flour, P1= Chickens given 3% fermented yellow pumpkin peel flour, P2= Chickens given fermented yellow pumpkin peel flour 6%, P3= Chickens given fermented yellow pumpkin peel flour 9% and P4= Chickens given fermented yellow pumpkin peel flour 12%. Based on the results of the study, the effect of giving fermented yellow pumpkin skin flour to super free-range chickens showed an unreal difference (P>0.05) on final body weight, weight gain, ration consumption and FCR. The use of fermented yellow pumpkin husk flour has the potential to be an alternative feed ingredient in the formulation of super free-range chicken rations, especially at the level of 12% which shows the lowest FCR value, which means better feed efficiency. The use of fermented yellow pumpkin husk flour at the level of 12% in super free-range chicken rations can be recommended as it results in the lowest FCR value (3.80) which indicates better feed use efficiency.